Alternating Directions Implicit Method for Solving Homogeneous Heat Diffusion Equation - Mahmood, Bushra Sh.; Gaftan, Awni M.; Fawzi, Firas A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
An Alternating Directions Implicit method is presented to solve the homogeneous heat diffusion equation when the governing equation is a bi-harmonic equation (X) based on Alternative Direction Implicit (ADI). Numerical results are compared with other results obtained by other numerical (explicit and implicit) methods. We apply these methods it two examples (X): the first one, we apply explicit when the temperature .